1987
DOI: 10.1016/0266-7681(87)90192-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1% lignocaine with 0.5% bupivacaine in digital ring blocks

Abstract: In a randomised double-blind trial comparing 1% lignocaine with 0.5% bupivacaine in digital ring block, the mean time of onset of complete anaesthesia was 5.8 minutes (range 5 to 10 minutes) for lignocaine and 11.2 minutes (range 8 to 20 minutes) for bupivacaine. The duration of action was 59.6 minutes (S.D. +/- 28.7 minutes) for lignocaine and 476 minutes (S.D. +/- 277 minutes) for bupivacaine. We describe how these differences can be exploited in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 4 publications
1
41
0
Order By: Relevance
“…Lidocaine with epinephrine is widely used in the acute care setting for procedural local anaesthesia because of its fast onset of action;9 many studies have shown it to be safe as a digital block 48. Our study shows that, in addition, it produces less pain at the time of injection.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Lidocaine with epinephrine is widely used in the acute care setting for procedural local anaesthesia because of its fast onset of action;9 many studies have shown it to be safe as a digital block 48. Our study shows that, in addition, it produces less pain at the time of injection.…”
Section: Discussionsupporting
confidence: 54%
“…From the literature comparing bupivacaine and lidocaine,9 10 we found that infiltration of bupivacaine and lidocaine may last for up to 6 h and 2 h, respectively. In another study, 2% lidocaine with epinephrine produced digital anaesthesia for an average of 10.4 h 1.…”
mentioning
confidence: 97%
“…The effect of lidocaine HCl, a component of TA, has been widely investigated for its effects on the cortisol response to castration of calves (Coetzee, 2011). One study found that 2% lidocaine HCl, injected into the testes and scrotum 15 min before castration, did not reduce the integrated cortisol response to surgical or burdizzo castration of Friesian calves (Fisher et al, 1996), despite significantly reducing cortisol concentrations from 0.25 to 1 h. Fisher et al (1996) suggested that this was likely attributable to the short duration of action (~1 h) (Reichl and Quinton, 1987) of lidocaine HCl. This suggestion is not suitable to explain the lack of difference between the integrated cortisol response of CTA and C calves in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…31 The onset of action for bupivacaine has been reported as 11.2 minutes (range 8 to 20 minutes). 31 The duration of action for digital block anesthesia for lidocaine has been reported between 60 minutes 31 and 4.9 hours. 32 Reichi and Quinton 31 reported a mean duration of action of bupivacaine of 7.9 hours (SD Ϯ 4.6 hours).…”
Section: Type Of Anestheticmentioning
confidence: 99%